A systematic review of Public-private partnership in construction industry from 1998 to 2021 - Yin, Chen; Mohamed, O.; Ye, Koh Mei (CENTRAL ASIA AND THE CAUCASUS, 2021)
The public-private partnership (PPP) has become a global concept to deliver the public facilities and services. Considerable studies on PPP have been made by researchers since it adopted in 1980s. Diverse research achievement can be seen in all kinds of journals. This paper conducted a content analysis of 498 articles between 1998 and the March of 2021 aims to provide a holistic review for the development of PPP mainly in construction field. Six journals consist of five construction journals and sustainability (Switzerland) were selected to analysis in detail pertain to the publication yearly, distribution of country or region, mainly project sectors involved, research methods used, and main research domains. The findings show that PPP research has been increasing yearly, and is developing rapidly. China surpassed the UK, HK, USA, became the country with the largest number of publications on PPP. In addition, 12 research topics were identified, along with the knowledge gaps and direction need to address in the future research.